Sera Level and Polymorphism of Interleukin-33 Gene in Iraqi Females Patients with Breast Cancer - Almohaidi, Asmaa M. Salih; Al-Abassi, Hazima Mossa; Abdulkareem, Zainab Jalil; Abdulkareem, Zainab Jalil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Interleukin-33 [IL-33] is a specific ligand for the ST2 receptor, and a member of theIL-1 family. It is a dual-function protein that acts both as an extracellular alarmin cytokine,and an as an intracellular nuclear factor participates in maintaining barrier function byregulating gene expression of IL-33 modulating tumor growth and anti-tumor immunity incancer patients. The present study aimed to investigate the role of IL-33 serum level and genepolymorphism in Iraqi women with breast cancer. Materials and methods: Blood sampleswere collected from 66 Iraqi patient women diagnosed with breast cancer, which were dividedinto two groups: pre-treatment [PT] and under treatment with chemotherapy [UTC] patients inaddition to 34 apparently healthy women who were matched with patients as a control.ELISA technique was used to determine the IL-33 serum level. The PCR-RFLP techniquewas performed to determine IL-33 gene polymorphisms at single nucleotide polymorphismSNP [rs1929992]. Results: IL-33 serum level recorded lower significant in PT [182.22 ±29.86pg/ml] and UTC [129.87 ± 45.11pg/ml] patients compared with control [258.08 ± 39.54 pg/ml] under [p